Formulation of Nb-doped ZnO nanoparticles towards improved photo conversion performance via luminescent down-shifting of the incident spectrum - Arith, Faiz; Jusoh, Yaumee Natasha; Aliyaselvam, Omsri Vinasha; Zainal, Nurul Aliyah; Mustafa, Ahmad Nizamuddin; Mohd Shah, Ahmad Syahiman; Salehuddin, Fauziyah (International Journal of Renewable Energy Development, 2025)
The quest for optimal solar energy utilization has prompted an investigation into materials and techniques, establishing luminescent down shifting (LDS). This method converts short-wavelength photons into longer wavelengths thus expanding the range of absorption. This may further enhance the efficiency of solar cell power conversion. Herein, the Zinc Oxide (ZnO) nanoparticle is introduced as a promising candidate for LDS, mainly due to its ability to convert light effectively and cost-savvy. This research delves into enhancing Niobium (Nb) doped ZnO particles that exhibit photoluminescent characteristics to improve energy conversion efficiency. The synthesis of 1% mol of Nb-doped ZnO nanoparticles on indium tin oxide (ITO) films was achieved using a low-temperature hydrothermal technique, varying the growth duration. Extensive analysis using XRD, SEM, and UV-Vis spectroscopy revealed that the optimal outcomes were achieved with an 8-hour growing period. The analysis revealed a hexagonal wurtzite crystal structure, characterized by prominent peaks on the (111) plane and a crystallite size of 37.18 nm. A morphology study indicated that the ZnO nanorods exhibited a randomly uniform oriented arrangement and a densely formed structure measuring 0.77 ± 0.02 μm. The samples exhibited promising optoelectronic properties based on the analysis, such as a characteristic bandgap of 3.35 eV, a transmittance of 46.54%, and an absorbance of 0.33 a.u .Furthermore, the electrical conductivity of the Nb-doped ZnO films was recorded at 1.62 mΩ⁻¹cm⁻¹.These findings suggest that controlling the Nb growth offers a promising avenue for optimizing the performance of Nb:ZnO nanoparticles for advanced solar energy conversion applications.